Exploring Portuguese physicians' perceptions of climate change impacts on health: A qualitative study - Nidia Ponte; Fátima Alves; Diogo Guedes Vidal (Elsevier, 2024)
Introduction: Health professionals, as primary responders to climate change health impacts, must be well-informed to effectively communicate adaptation risks and benefits to influence both patients and organizations. This study was undertaken in order to survey how physicians in Portugal understand, explain, and experience the impacts of climate change on health in their clinical practice. Understanding physicians' knowledge level on this subject also can help determine whether training is needed, and through what educational mechanisms. Material and methods: Using a semi-structured interview script, this study applied a qualitative methodology with interviews of 13 physicians from various medical specialties in Portugal, aged 28 to 73. Results: All participants recognized that human action is the main contributor to climate change, indicating that fossil fuels and overproduction are the main factors responsible for greenhouse gas emissions. They also agreed that climate change affects human health. However, they reported that they find connecting diseases to climate change challenging in their clinical practice, and expressed the need for training on the effects of climate change on health. Conclusion: This study demonstrated that physicians recognized the importance of understanding and communicating the connection between climate change and health in their daily practice, and that failure to recognize these impacts may affect appropriate diagnosis and preparedness for extreme climate events. These results highlight the urgency of addressing the health impacts of climate change and underscore the role of education and awareness.